FIRST AMPHIBIAN FIND IN EARLY PERMIAN FROM SARDINIA (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
An amphibian fauna from Permo-Carboniferous boundary beds is recorded for the first time in Italy. A thin fossiliferous level has been found in the Perdasdefogu Basin in southeastern Sardinia;it yields several speciments of Branchiosaurus cf."B." petrolei Gaudry 1875), often in mass mortality assemblages.Repeated mass mortality events testify to sudden changes in the environment of the basin, possibly due to seasonal variations. The finding of speciments very close to Branchiosaurus petrolei,which is a common species in the Central France basins,confirms that Sardinia at the time belonged to the same hydrographic basin of continental Europe, with no seaway in between.Furthermore, though not the primary focus of this note, we report the first discovery of the xenacanth teeth and acanthodian spines in Italy.